Overcoming Obstacles: A Case Report of Preterm Neonatal Respiratory Distress Syndrome with Coexisting Hydrocephalus, Aqueductal Stenosis, and Neonatal Hyperbilirubinemia - Parth Balvantbhai Chanv; Simbita Marwah; Sargam Bhatt; Kiran Goplani; Suhani Nayak; Uma Nayak (Indian Journal of Medical Biochemistry)
Aim: The aim of present report is to describe the diagnosis and management of a preterm neonate with coexisting respiratory distress syndrome (RDS), hydrocephalus, aqueductal stenosis, and neonatal hyperbilirubinemia (NNH). Background: A 31-day-old preterm male infant with RDS, neonatal hyperbilirubinemia, Intrauterine growth restriction (IUGR), aqueductal stenosis, and hydrocephalus was admitted to the neonatal intensive care unit (NICU) and received oxygen support and double volume exchange transfusion. Physical examination showed yellow skin discoloration, triangular facies, moderate hepatosplenomegaly, and hypertonia. A hematological workup revealed anemia, leukocytosis, Staphylococcus haemolyticus growth, and elevated bilirubin levels. Ultrasonography (USG) brain showed dilated ventricles and aqueduct effacement, leading to the diagnosis of hydrocephalus due to aqueductal stenosis, and a positive toxoplasmosis, rubella cytomegalovirus, herpes simplex, and HIV (TORCH) test. Case description: A 31-day-old preterm male infant with multiple medical conditions, including RDS, hyperbilirubinemia, IUGR, aqueductal stenosis, and hydrocephalus, was admitted to the NICU for 30 days. The baby showed yellow skin discoloration, triangular facies, moderate liver/spleen enlargement, hypertonia, and anemia. USG brain showed dilated ventricles and aqueduct effacement, leading to a diagnosis of hydrocephalus due to aqueductal stenosis. The baby was also diagnosed with TORCH (Toxoplasma) positive. Conclusion: The present case report highlights the complexity and challenges associated with managing a preterm male infant with multiple medical conditions. The diagnosis of RDS, neonatal hyperbilirubinemia, IUGR, aqueductal stenosis, and hydrocephalus required a comprehensive approach, including oxygen support, double volume exchange transfusion (DVET), and hematological workup. The management of the infant’s conditions emphasized the importance of prompt and accurate diagnosis and aggressive treatment strategies. The successful outcome in this case, highlights the potential of multidisciplinary approaches in improving the prognosis of infants with multiple medical conditions and emphasizes the need for continuous monitoring and intervention to ensure optimal outcomes. Clinical significance: Clinical significance refers to the practical importance or real-world impact of the findings or information presented in the case report. It highlights how the case report contributes to the current understanding of a medical condition, its diagnosis, and treatment, and how it can help improve patient care. In a case report, the clinical significance is often summarized in the conclusion and highlights the important takeaways for healthcare professionals.